Perspectives on Heidegger’s Overcoming Nihilism in Dialogue with East Asian Thought Traditions - Vėželis, Tautvydas (Problemos, 2023)
The article analyzes the perspectives of overcoming nihilism (Verwindung) by discussing Heidegger’s relationship with East Asian traditions of thought (first of all, chan/zen and daoism). We can consider the emergence of Enframing (Gestell or Ge-stell) of the essence of modern technology defined by the philosopher as a diagnosis of the fulfillment of nihilism and the end of the Western tradition of thought. By revealing the problem of the end of the Western metaphysical tradition and its overcoming, the aim is to understand the possibilities of the emergence of a different way of thinking by looking at the horizon of post-metaphysical thinking. Heidegger’s dialogue with the sources of Eastern thought is a search for perspectives on overcoming nihilism (Verwindung), which is inseparable from the deepening of self, other and mutual understanding.